Exploring Thermal Dynamics in Wound Healing: The Impact of Temperature and Microenvironment - Huang J; Fan C; Ma Y; Huang G (Dove Medical Press, 2024)
Jun Huang,1,2 Chunjie Fan,2 Yindong Ma,2 Guobao Huang2 1Department of Clinical Medicine, Shandong Second Medical University (Weifang Medical University), Weifang, 261000, People's Republic of China; 2Department of Burns and Reconstructive Surgery, Central Hospital Affiliated to Shandong First Medical University, Jinan, 250013, People's Republic of ChinaCorrespondence: Guobao Huang, Department of Burns and Reconstructive Surgery, Central Hospital Affiliated to Shandong First Medical University, No. 105, Jiefang Road, Lixia District, Jinan, Shandong Province, 250013, People's Republic of China, Tel +86 531-55865707, Email huangguobao@sdu.edu.cnAbstract: Exploring the critical role of thermal dynamics in wound healing, this manuscript navigates through the complex biological responses initiated upon wound infliction and how temperature variations influence the healing trajectory. Integrating biothermal physics, clinical medicine, and biomedical engineering, it highlights the significance of thermal management in wound care, emphasizing the wound microenvironment's division into internal and external domains and their collaborative impact on tissue repair. Innovations in real-time wound temperature monitoring, especially through intelligent wireless sensor dressings, are spotlighted as transformative, enabling precise wound condition management. The text underscores the necessity for further research to elucidate thermal regulation's molecular and cellular mechanisms on healing processes. It advocates for standardized protocols for localized heating treatments, integrating them into personalized wound care strategies to enhance therapeutic outcomes, improve patient well-being, and achieve cost-effective healthcare practices. This work presents a forward-looking perspective on refining wound management through sophisticated, evidence-based interventions, emphasizing the interplay between thermal dynamics and wound healing.Keywords: wound healing, thermal dynamics, wound microenvironment, intelligent dressings, localized heating treatment